EFFICACY OF GOSERELIN FOR POST-OPERATIVE TREATMENT IN CHINESE PATIENTS WITH MODERATE TO SEVERE ENDOMETRIOSIS: AN OBSERVATIONAL, MULTICENTRE, OPEN-LABEL, NON-INTERVENTIONAL STUDY - Jinghe Lang; Zhou, Yingfang; Leng, Jinhua; Zheng, Jianhua; Guan, Zheng; Fang, XIAOLING; Lin, Jun; Zheng, Ai; La, Duanduan; Zhang, Shulan; et al. (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objective: The aim was to assess the efficacy of post-operative adjuvant treatment with goserelin acetate for reducing the recurrence of pelvic symptoms and total recurrence rates in Chinese patients with moderate to severe endometriosis. Methods: This largest non-interventional, observational study enrolled 426 Chinese patients with moderate to severe endometriosis across 15 centers in China. Goserelin acetate depot (3.6 mg) was prescribed as adjuvant post-operative treatment, subcutaneously every 4 weeks till 18 months. The primary efficacy end-point was improvement of pelvic symptom recurrence rate and total recurrence rates (including pelvic symptom and physical findings) up to 18 months post-surgery. Secondary endpoints were pregnancy rate among infertile subjects receiving post-operative goserelin treatment 18 months following the operation; and information on goserelin administration. Results: The total recurrence rate (8.2%; 95% confidence interval [CI], 5.8-11.3%) and symptom recurrence rate (5.6%; 95% CI, 3.6-8.2%) in Chinese patients with moderate to severe endometriosis was comparatively lower than the previously reported studies. Less than 28% of the patients required add-back therapy to offset the effects of gonadotropin-releasing hormone (GnRH), and indicated that the GnRH agonist was efficacious in the majority of the patients. No serious adverse events were reported during the study. Conclusion: Goserelin acetate was effective in reducing symptom and total recurrence rate when used post-operatively in Chinese patients with mild to severe endometriosis. The authors therefore offered goserelin acetate as a viable treatment for Chinese patients with moderate to severe endometriosis. Keywords: Endometriosis, Gonadotropin-releasing hormone, Goserelin acetate, Pelvic symptom recurrence rate, Infertility, Pregnancy rate.